Christian-Muslim Dialogue - Malek, George N. (Missiology, 1988)
This article reviews the postwar development of the Western concept of Islam in light of the present conflicts between the Middle East and the West, and analyzes Christian mission through an historical, psychological examination of the motive of postwar Christian mission to the Middle East. It then presents the problem of Christian/Muslim relations in light of the fundamental issue facing the two sides, that is, religious misunderstanding, not political or economic interaction. The article then raises questions on the method and motive of postwar Christian mission to the Middle East, suggesting an alternative method for future mission.The paper takes the position that dialogue is the most productive form of contact between Christianity and Islam. It attempts to indicate, by critical examination, the potential points of tension, error, and reconciliation in the theological thinking of both. A major contribution of the paper is its affirmation and definition of a dialogue, its method and motive. Finally, the paper charts some solutions, theologically, psychologically, and cross-religiously.